Teacher Management Strategies for Enhancing Hafiz Al-Qur'an Competence in the Digital Era - Arina, Arina Nur Sofiana; Na'imah; Rizqa Tamia, Dewi; Adawiyah, Miftahul (el-Tarbawi, 2024)
This study explored teacher management strategies for enhancing the competence of Hafizh Al-Qur'an in the digital era. This qualitative descriptive study collected data through interviews, observations, and documentation. The data were validated using triangulation techniques, including data triangulation, investigator triangulation, theory triangulation, and methodological triangulation. The findings of this study indicate an increase in the competence of Hafizh Al-Qur'an including higher motivation, improved reading and memorization quality, increased consistency and discipline, and deeper understanding and practice of the Al-Qur'an. This improvement is attributed to effective management practices through the Planning-Organizing-Actuating-Controlling approach. Planning includes identifying training needs, setting strategic goals, and planning digital technologies. Organizing includes resource allocation, team building, and the provision of facilities. Actuating includes teacher training, implementation of the Tahfizh method, and use of the online platform. Control includes periodic evaluation, feedback, and obstacle fixing. This study offers a foundation for future research to explore potential challenges and mitigation strategies for the potential negative impacts of using technology in learning and memorizing the Qur'an.